Application of molecular imaging combined with genetic screening in diagnosing MELAS, diabetes and recurrent pancreatitis - Zhiping, Wang; Quwen, Li; Hai, Zhou; Jian, Zhou; Peiyi, Gao (Folia Neuropathologica, 2016)
Aim: We report molecular imaging combined with gene diagnosis in a family with 7 members who carried an A3243G mutation in mitochondrial tRNA and p.Thr 137 Met in cationic trypsinogen (PRSS1) gene presented with mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes (MELAS), diabetes, and recurrent pancreatitis. Material and methods : DNA sequencing was used to detect and validate mitochondrial DNA and PRSS1. We also verified that mitochondrial heterozygous mutations and c.410 C>T mutation causing p.Thr 137 Met could be detected in oral epithelial cells or in urine sediment cells. In addition, molecular imaging was carried out in the affected family members. Results : In this pedigree, MELAS syndrome accompanied by pancreatitis was an important clinical feature, followed by diabetes. Heteroplasmy of the mtDNA A3243G and c.410 C>T mutation of PRSS1 was found in all tissue samples of these patients, but no mutations were found in 520 normal control and normal individuals of the family. However, based on molecular imaging observations, patients with relatively higher lactate/pyruvate levels had more typical and more severe symptoms, particularly those of pancreatic disease (diabetes or pancreatitis). Conclusions : MELAS syndrome may be associated with pancreatitis. For the diagnosis, it is more reasonable to perform molecular imaging combined with gene diagnosis.